Development of Hypertext-Based Teaching Materials in Curriculum and Learning Courses during the Covid-19 Pandemic - Ira Arini; Dedi Aryadi; Usmaedi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This study aims to develop hypertext-based teaching materials during the Covid-19 pandemic so that they can effectively improve learning outcomes for Curriculum and Learning courses. The development of teaching materials follows the steps of developing the Rowntree model with the stages of preliminary research, development planning, validation, evaluation and revision (expert judgment review, face to face, filed test), and implementation. The value of product development obtained from the review of material experts is 3.12, instructional design experts are 3.68, and design and layout experts are 3.72. The average results obtained from the face to face and field tests are 3.55. At the implementation stage, the results of the pretest showed a value of 65.5 and the results of the posttest showed a value of 82.7. This shows that the product development of hypertext-based teaching materials is feasible to use and can effectively improve learning outcomes for Curriculum and Learning courses.